Corporate Social Responsibility Dan Kinerja Keuangan Perusahaan; Sebuah Kajian Literatur - Muhammad Faisal Arif; Wa Ode Rayyani (Insan Cita Bongaya Research Journal, 2024)
The purpose of this study is to examine research that examines the effect of CSR on financial performance both directly and by using mediating variables. Methodology, this research is in the form of a literature review of 16 articles published in journals affiliated with Emerald Publishing Limited and Scopus indexed. Findings, this study found mixed results regarding the influence of CSR on financial performance and with the use of mediating variables. In addition, several measurements of CSR variables such as ESG, GRI, and KLD Data and financial performance are measurements dominated by short-term (ROA and ROE) and long-term (Tobin'Q) performance and some measurements are mediating variables. Implications, and theoretical implications with research on companies in various countries including countries in one region. The diversity in the use of variable measurements in research provides broad insights. Practical implications, provide information on how CSR affects financial performance. Limitations, this study only examines articles published in journals affiliated with Emerald Publishing Limited and does not examine the existence of control variables in the study